Synthesis of thermally spherical CuO nanoparticles - Nittaya Tamaekong (2018)
Copper oxide (CuO) nanoparticles were successfully synthesized by a thermal method. The CuO nanoparticles were further characterized by thermogravimetric analysis (TGA), differential thermal analysis (DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectrometry (EDS), and high resolution transmission electron microscopy (HRTEM), respectively. The specific surface area (SSABET) of CuO nanoparticles was determined by nitrogen adsorption. The SSABETwas found to be 99.67 m2/g (dBETof 9.5 nm). The average diameter of the spherical CuO nanoparticles was approximately 6-9 nm. © 2014 Nittaya Tamaekong et al.